If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 24 = 5x + 4 Reorder the terms: 24 + 3x = 5x + 4 Reorder the terms: 24 + 3x = 4 + 5x Solving 24 + 3x = 4 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 24 + 3x + -5x = 4 + 5x + -5x Combine like terms: 3x + -5x = -2x 24 + -2x = 4 + 5x + -5x Combine like terms: 5x + -5x = 0 24 + -2x = 4 + 0 24 + -2x = 4 Add '-24' to each side of the equation. 24 + -24 + -2x = 4 + -24 Combine like terms: 24 + -24 = 0 0 + -2x = 4 + -24 -2x = 4 + -24 Combine like terms: 4 + -24 = -20 -2x = -20 Divide each side by '-2'. x = 10 Simplifying x = 10
| 2(5x-1)-(7x-5)=8-(3x+2) | | 2x^3+7x^2+2x-3=0 | | .2x+27=22 | | 3x+2x-4=21 | | -(2)(-5)= | | -5(2y-3)=3(1-4y)+13 | | 0.15x=40+0.15x | | 8-.33333333x=16 | | 8c+6=54 | | 2(x+4)+2x=4x-1 | | (X-3)2x=57 | | 10x+5=2x+20 | | 0.15=40+0.05 | | -6=x+4 | | -7.1(-4.4m+3.6)=-3.5+.4(7.9+3.503) | | (2b^4)-9=83 | | 2k-1+k+2+k-2+k-1+k+2=24 | | (x-12)x+y(y+6)=19 | | 3m+4=2m-30 | | 4x+6=6x+6 | | x^2+y^2-12x+6y=19 | | -6(5n+8)+4(8n+6)=-16 | | 5-.50x=-9 | | 4-(x+.2)=2x-.1 | | (2b+3)2+2(2b+3)=477 | | 9x+-3=24 | | 6p+24=-2p | | 3x+2=-31+6x | | 2x^2-39x-120=0 | | 1.5(2b+6)+9=24 | | n-14=30 | | -6(p+1)=-6(p+1)-10 |